Evaluation of multidrug-resistant bacteria and their molecular mechanisms found in small animal veterinary practices in Portugal - Moreira da Silva, Joana; Menezes, Juliana; Fernandes, Laura; Marques, Cátia; Costa, Sofia Santos; Timofte, Dorina; Amaral, Andreia J.; Pomba, Constança (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionIntensive medical care provided in companion animal practices carries the potential risk of selecting and disseminating multidrug-resistant organisms (MDROs). However, data on infection, prevention and control standards specific to small animal veterinary practices (SAVPs) remains limited. The goal of our work was to evaluate the environmental contamination and staff carriage by MDROs in veterinary practices across Portugal.MethodsFourteen SAVPs were enrolled. Environmental samples were collected from critical areas such as operating room, wards and pre-operative area. Veterinary team members voluntarily gave nasal, hand and rectal swabs. All samples were screened for the presence of, including extended-spectrum β-lactamases (ESBL)- and carbapenemase-producing Gram-negative bacteria and methicillin-resistant Staphylococcus spp. (MRS). Whole-genome sequencing was performed for carbapenem resistant strains.ResultsEnvironmental evaluation by surface swabs revealed that 6.5% (n=32/490) were contaminated with multidrug-resistant Gram-negative bacteria. OXA-23-producing Acinetobacter spp. (n=5) and IMP-8-producing Pseudomonas juntendi (n=2) strains were described on different locations of different SAVPs. Moreover, Stenotrophomonas maltophilia (n=12) and Pseudomonas aeruginosa (n=3) strains were also found on multiple surfaces of different SAVPs. Three human samples (two rectal, one hand) had carbapenem-resistant P. aeruginosa strains by OprD mutations, while S. maltophilia strains were recovered from four samples (two rectal, two hands). One nasal swab was positive for carbapenem-resistant Klebsiella pneumoniae ST11. Only one SAVP surface was positive for the newly typed for methicillin-resistant Staphylococcus aureus (MRSA) ST9220-II. MRSA nasal carriage was found in 14% of samples (n=9/64), with an equal prevalence of ST22-IV and ST8-VI. As for hand samples, MRSA was present in 10.7% (n=4/38), with a predominance of ST8-VI.DiscussionThese emerging data indicate that SAVPs may significantly contribute to the dissemination of MDROs. To address this, rigorous infection, prevention and control (IPC) measures should be implemented, alongside educational workshops directed to all veterinary staff as well as to veterinary and nursing students.